PENGARUH KINERJA LINGKUNGAN TERHADAPKINERJA EKONOMI - Dewi, Ni Kadek Nyupina; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of environmental performance on economic performance. Environmental performance is proxied by PROPER and economic performance is calculated by using stock returns. The samples used in this study are 22 companies listed in the Indonesia Stock Exchange and the PROPER program in 2013-2015 with 66 observations. The sampling method used is the method nonpropability sampling with purposive sampling technique. Data analysis technique used is a simple linear analysis.Based on the analysis found that environmental performance does not affect the economic performance demonstrated by the significant value of 0.991> 0.05.